Online Shopping Intentions Of Tiktokshop Consumers: The Influence Of Consumer Privacy and Shopping Enjoyment Study in Department Management of Universitas Simalungun - Saragih, Liharman; Ginting, Fauziah Aftitah; Haidir, Sharla Nasyawa; Rahayu, Elwi Sri; Harahap, Dwi Putri Aisyah; Okista, Rizky (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
In this study, researchers made a study entitled